Vertical Axis Wind Turbine - Raj Kamal, M. D.; Harish Krishna, P.; Jagadeesh Babu, G.; Suresh, Ashwin; Baskar, K. (Asian Review of Mechanical Engineering, 2017)
The main objective of this paper is to design the vertical axis wind turbine. The design of the turbine will include the study of various vertical axis wind turbines. Various wind turbines converting wind energy to a rotary motion have been already suggested and practiced. Among them, the horizontal axis wind turbine is required to have the propeller rotating disk always rightly aligned with the wind direction, whereas the vertical axis wind turbine is Omni-directional, is not influenced at all by the wind direction and is better in respect of the configuration and operation.